2012
DOI: 10.1002/hyp.9393
|View full text |Cite
|
Sign up to set email alerts
|

The influence of salinity on hysteresis of soil water‐retention curves

Abstract: Taiwan is surrounded by the sea, and the southwestern seashores are suffering from a growing land subsidence problem caused by the excessive extraction of groundwater. There is also very serious intrusion by seawater along the coastline. These circumstances obstruct any land use, soil remediation or agriculture development in the area. When seawater intrudes, salt gets into the soil. The infiltration, evapotranspiration and the distribution of salinity in the unsaturated soil become a very complex problem. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The WSIs are equivalent to the SWCC at the dry end. Some studies have revealed an effect of soil salinity on SWCCs: an increase in salinity causes the SWCC to move upward, thus increasing the maximum water content and resulting in a stronger hysteresis effect (Ma et al, ; Tan et al, ; Wang, Dang, & Yang, ; Zhao et al, ). Similar trends were also observed with increasing salinity in this study (Figure , Figure and Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WSIs are equivalent to the SWCC at the dry end. Some studies have revealed an effect of soil salinity on SWCCs: an increase in salinity causes the SWCC to move upward, thus increasing the maximum water content and resulting in a stronger hysteresis effect (Ma et al, ; Tan et al, ; Wang, Dang, & Yang, ; Zhao et al, ). Similar trends were also observed with increasing salinity in this study (Figure , Figure and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…High salt content changes the morphology and structure of soil, increases the osmotic pressure of the soil solution, and eventually causes physiological drought of plants (Hu, ; Ma, Li, Wu, & Huang, ; Parida & Das, ; Xu, Zeng, Wu, & Huang, ; Zeng, Xu, Huang, Wu, & Tuller, ). Specifically, salinity can increase the proportion of small pores in soil, improve the capacity for soil water retention and enhance soil pore water suction, which leads to the upward shift of the soil water characteristic curve (SWCC, soil matric potentials > − 1.5 MPa) and the increase of the hysteresis effect (Ma, Lin, & Tan, ; Tan, Wu, Li, & Huang, ; Zhao, Zhang, & Yu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unreasonable fertilizer application and irrigation can exacerbate soil salinization (Litalien and Zeeb, 2020). Thus, soil salinization is a common global problem (Ma et al, 2013;Perri et al, 2017;Shi et al, 2021;Taghizadehghasab et al, 2021). Alluvial farmland is the optimal farmland type in the Loess Hilly area of China, with high soil water contents, fertility, and crop yields (Chen et al, 2019;Xu et al, 2018;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%